THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ABILITY OF THE EIGHTH GRADE STUDENTS OF SMPN 5 MENGWI IN ACADEMIC YEAR 2021/2022 - Melania Putu Trisnayanti; Ni Made Wersi Murtini; Luh Ketut Sri Widhiasih (Academic Journal on English Studies (AJOES), 2022)
Ex post facto correlational research was used as the design of this research to find out the significant correlation between grammar mastery and writing ability of the eighth-grade students of SMPN 5 Mengwi in academic year 2021/2022. Grade eight students from SMPN 5 Mengwi were used as the population for this study and through sampling method using lottery system, 64 students were selected as samples. Data were collected by through a writing test and a paragraph construction test. Pre-requisite analysis and hypothesis testing were performed to analysed the data obtained. The data were found to be normally and homogeneously distributed. As a result of the hypothesis test, the alternative hypothesis (Ha) was confirmed. In short, the findings confirm a significant correlation between grammar mastery and writing ability of the eighth-grade students of SMPN 5 Mengwi in academic year 2021/2022. Therefore, the result of the study can be used as the reinforcement for a teacher to teach grammar to the students, since a good grammar mastery can give an opportunity to have a better writing ability.